Problem Solving dalam Metode Pembelajaran IPS - Kabakoran Inayah; Victor Novianto (Proceedings Series on Social Sciences & Humanities, 2023)
Learning is the process Social Science or Social Studies Education is a very important lesson in a person's life, where learning social studies education has a very large and noble goal, among others, to understand and develop knowledge, values, attitudes, social skills, citizenship, facts, events, concepts and generalizations and be able to reflect them into the life of society, nation and state. This research uses the type of Classroom Action Research (PTK) using the action research model of Kemmis and Taggart. Students who did not reach the KKM score were more, namely 18 students (64.2%). this allows it to be done or the right method is needed to improve student learning achievement in order to reach the KKM score. the next day the problem solving method was applied on April 10, 2023, for cycle I, this application was carried out with II cycles on April 11, 2023. In cycle I there was an increase in the category of very good students increased by about 3 students (11%), and good as many as 12 students or 43%, while the moderate category decreased by about 13 students (46%). Student learning activeness began to increase and was seen in cycle II where the excellent category amounted to 8 students (28.5%), good around 15 students (18%) and the moderate category decreased to the remaining 5 students (18%). This also occurred in the increase in students' KKM scores which improved in cycle I 19 students (68%) and in cycle II increased to 25 students (89%). Keywords: Learning Methods, Social Science, Problem Solving.